PERTAMBAHAN BERAT BADAN, JUMLAH KONSUMSI DAN EFISIENSI PENGGUNAAN PAKAN BABI FASE GROWER SAMPAI FINISHER YANG DIBERI GULA AREN (Arenga pinnata Merr) DALAM AIR MINUM - Poluan, Wenny R; Montong, Petrus R.R.I; Paath, Jantje F; Rawung, Vonny R.W (Universitas Sam Ratulangi, 2017)
Weight gain, feed consumption and the efficiency of growing pigs to slaughter with palm sugar in drinking water. The production performances by looking at weight gain, consumption and feed efficiency is part of the requirements to see pig production capabilities. The study lasted 10 weeks consisting of 8-week data collection period and 2 weeks of data collecting preliminary aims to determine the effect of the use of palm sugar in the drinking water to the performances ofÂ grower to finisher productivities of pigs. The study used 16 mix male and female pigs period grower 12-14 week-old offspring of type cross-bred Yorkshire and Landrace. The experimental design used in this research was Block Randomized Experimental Design with four levels of treatment as follows 0, 2%, 4%, 6% palm sugar in drinking water in four different weight groups as replication. The analysis of variance (ANOVA) showed that the use of palm sugar in drinking water on weight gain (0,57- 0,65 kg) significantly effect (P <0.05), while the amount of consumption (2,56- 2,64 kg) Â and feed efficiency (0,22-0,25) were not significantly different (P> 0.05), however the amount of water consumption drink (6,57-8,91 litre) indicates the effect of significantly (P <0.05). The use of palm sugar in drinking water in pigs grower phase until finisher can deliver good growth despite the amount of consumption and the efficiency of feed use remains the same. Â Key words ; Grower, finisher, palm sugar